Dinuclear Nickel(II) and Copper(II) Complexes of 8‐Quinoline‐1H‐pyrazole‐3‐carboxamide: Crystal Structure, Magnetic Properties, and DFT Calculations. Issue 18 (2nd May 2021) - Mohammadnezhad, Gholamhossein; Ahfad, Neda; Meghdadi, Soraya; Farrokhpour, Hossein; Schmitz, Simon; Haseloer, Alexander; Buchholz, Axel; Plass, Winfried; Klein, Axel
Abstract: Homoleptic dinuclear complexes [M2 (qpyzc)2 ] (M=Cu (1 ) or Ni (2 ) were obtained from the readily synthesised trischelate pyrazole‐based qpyzc ligand (H2 qpyzc=8‐quinoline‐1 H ‐pyrazole‐3‐carboxamide). Their crystal and molecular structures, magnetic properties, and UV‐vis spectra were reported alongside with DFT and TD‐DFT calculations. Trigonality index τ'4 values of 0.25 and 0.21 for the Cu and Ni centres, respectively reveal a marked distortion from square planar geometry. The two metal coordination planes within a complex are tilted towards each other with 40.2(1)° for Cu(II) and 34.5(2)° for Ni(II). The central six‐membered M2 N4 metallocycle is almost planar and the two anionic pyrazolate rings are tilted towards each other by 37.4(1)° (1 ) and 38.5(2)° (2 ), respectively. Regardless of this peculiar bonding situation magnetic measurements on 1 are in line with medium‐sized antiferromagnetic coupling with a coupling constant of J =−100 cm −1, an isotropic g value of 2.11 and an S =0 ground state. Complex 2 seems to be diamagnetic. DFT calculations gave an excellent agreement between calculated and experimental metrics of the complexes and supported the prevalence of the singlet ground state for 1 . TD‐DFT calculated UV‐vis absorption spectra agree well with observed absorptions and the red colour of both compounds. Abstract : Nickel(II) and copper(II) form dinuclear planar complexes [M2 (qpyzc)2 ] with the tridentate and bridging 8‐quinoline‐1 H ‐pyrazole‐3‐carboxamide. XRD, EPR magnetic properties, and UV‐vis spectra were reported alongside with the results of DFT and TD‐DFT calculations.